Gardening Learning Methods Increase Responsibility in Early Childhood - Jayadiningrat, Made Gautama; Dapet, Ni Wayan; Suyanta , I Wayan (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Children's lack of responsibility can be seen in small things. Therefore, it is essential to stimulate the character of responsibility in early childhood as early as possible so that children have a good attitude of responsibility. This study aims to analyze the method of learning gardening and the attitude of responsibility of children in kindergarten. This study uses a quasi-experimental method with a nonequivalent control group design. The population of this study was 43 early childhood children. The technique used in collecting samples was purposive sampling, so the sample of this study was 43 early childhood children. The data collection method used observation and documentation. The data collection instrument in this study used observation guidelines. The data analysis technique used inferential statistical analysis with the SPSS 25 program. The results of this study showed a significant difference between the control class and the experimental class. The results of the data analysis showed that there was an influence between the method of learning gardening and the attitude of responsibility of children. It was concluded that the method of learning gardening can improve the attitude of responsibility in students. This study implies that teachers can foster children's attitude of responsibility through the application of the method of learning gardening.